C–H Polyaddition of Dimethoxyarenes to Unconjugated Dienes by Rare Earth Catalysts - Shi, Xiaochao; Nishiura, Masayoshi; Hou, Zhaomin (Journal of the American Chemical Society, 2016)
The C–H polyaddition of dimethoxyarenes such as 1,4-dimethoxybenzene and 4,4′-dimethoxybiphenyl to unconjugated dienes such as norbornadiene and 1,4-divinylbenzene has been achieved for the first time by using cationic half-sandwich rare earth alkyl catalysts. This protocol afforded novel polymer materials consisting of dimethoxyarene moieties and nonpolar hydrocarbon structure motifs (cyclic, linear, and aromatic) in perfectly alternating sequences that are otherwise difficult to make. The reaction proceeded via CC double bond insertion into a C–H bond ortho to each of the two methoxy groups in a step-growth polymerization fashion.